PENGEFEKTIFAN PEMBELAJARAN MENULIS EKSPOSITORI MELALUI IMPLEMENTASI PENDEKATAN PROSES DI SEKOLAH DASAR - Suhel Madyono (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
The purpose of this research was to describe the implementation of process approach in teaching expository writing in the elementary school. The approach of the research was qualitative with classroom action model research. The subjects of the research were 9 students. The result of the research indicated that the implementation of process approach in teaching expository writing was effective.